2018
DOI: 10.1371/journal.pone.0200633
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of KRAS, DDR2, and TP53 gene mutations in lung cancer: An analysis of Iranian patients

Abstract: PurposeLung cancer is the deadliest known cancer in the world, with the highest number of mutations in proto-oncogenes and tumor suppressor genes. Therefore, this study was conducted to determine the status of hotspot regions in DDR2 and KRAS genes for the first time, as well as in TP53 gene, in lung cancer patients within the Iranian population.Experimental designThe mutations in exon 2 of KRAS, exon 18 of DDR2, and exons 5–6 of TP53 genes were screened in lung cancer samples, including non-small cell lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 67 publications
(73 reference statements)
1
25
0
Order By: Relevance
“…Exploring the genetic background of different populations is of great significance to predict lung cancer patients’ response to immunotherapies. 11 In the application of ICIs, immune-related adverse events (irAEs) are the key monitoring items in clinical practice. The incidence of all grade irAEs is 22%, and that of high-grade irAEs is 4%.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the genetic background of different populations is of great significance to predict lung cancer patients’ response to immunotherapies. 11 In the application of ICIs, immune-related adverse events (irAEs) are the key monitoring items in clinical practice. The incidence of all grade irAEs is 22%, and that of high-grade irAEs is 4%.…”
Section: Discussionmentioning
confidence: 99%
“…The main feature that characterizes these "niche" mutations is their low prevalence in the population of patients with lung cancer when compared with KRAS and EGFR. In the present study, we identified these "niche mutations" on the basis of a population prevalence that was equal to or less than 10% based on literature data [8][9][10]. In particular, according to recently published data concerning 14 healthcare institutions in the US, the prevalence for these mutations was as follows: KRAS 25%, EGFR 23%, HER2 2.7%, BRAF 2.6%, PIK3CA 0.8%, NRAS 0.7%, c-MET 0.7%, and MAP2K1 0.3% [8].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, according to recently published data concerning 14 healthcare institutions in the US, the prevalence for these mutations was as follows: KRAS 25%, EGFR 23%, HER2 2.7%, BRAF 2.6%, PIK3CA 0.8%, NRAS 0.7%, c-MET 0.7%, and MAP2K1 0.3% [8]. Moreover, the prevalence of the RET mutation in adenocarcinoma was estimated to be 1.7% [9], and the prevalence of DDR2 mutation in lung cancer was 2.2% [3,10]. Overall, the KRAS mutation was considered to be the most lethal mutation, exhibiting the worst prognosis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…DNA extraction was performed based on the classic phenol-chloroform extraction method with some modifications 26 , 27 . Briefly, 20 mg of the tissue sample was homogenized in 400 μl of lysis buffer (10 mM NaCl, 20 mM Tris-HCl, 1 mM EDTA, pH=8), 50 μl of 10% SDS, and 25 μl of proteinase k (10 mg/ml ).…”
Section: Methodsmentioning
confidence: 99%